PERAN PROGRAM MAKAN GIZI GRATIS DALAM MENDUKUNG KETAHANAN PANGAN NASIONAL - Riski Sahyuri; Maryam Batubara (Smart Education, 2026)
Abstract: This study aims to analyze the role of the Free Nutritious Meal Program in supporting national food security in Indonesia, which encompasses not only food availability but also access, nutritional quality, and the stability of community consumption. The research employs a descriptive qualitative approach using the Analytic Network Process (ANP) method to identify key factors and determine strategic priorities in program implementation. Data were collected through interviews and questionnaires based on expert judgment, as well as documentation studies from various official sources. The results indicate that the program significantly contributes to improving access to nutritious food, particularly for vulnerable groups, strengthening local food supply chains through increased demand for domestic agricultural products, and promoting the empowerment of farmers and small and medium enterprises. In addition, the program plays an important role in maintaining food consumption stability, reducing the risk of food insecurity, and enhancing community welfare. However, its successful implementation is influenced by several key factors, including government policy consistency, budget availability, the quality of human resources, and the effectiveness of distribution and monitoring systems. Therefore, strong synergy among stakeholders is essential to ensure the sustainability and optimization of the program in supporting national food security in a sustainable manner. Keywords: Programme MBG, Food Security, Analytic Network Process, Food Supply Chain, MSME Empowerment Abstrak: Penelitian ini bertujuan untuk menganalisis peran Program Makan Bergizi Gratis dalam mendukung ketahanan pangan nasional di Indonesia, yang tidak hanya mencakup aspek ketersediaan pangan tetapi juga akses, kualitas gizi, dan stabilitas konsumsi masyarakat. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode Analytic Network Process (ANP) untuk mengidentifikasi faktor kunci serta menentukan prioritas strategi dalam implementasi program. Data diperoleh melalui wawancara dan kuesioner berbasis expert judgement serta studi dokumentasi dari berbagai sumber resmi. Hasil penelitian menunjukkan bahwa program ini berkontribusi signifikan dalam meningkatkan akses terhadap pangan bergizi, khususnya bagi kelompok rentan, memperkuat rantai pasok pangan lokal melalui peningkatan permintaan produk domestik, serta mendorong pemberdayaan petani dan pelaku UMKM. Selain itu, program ini juga berperan dalam menjaga stabilitas konsumsi pangan, mengurangi risiko kerawanan pangan, dan meningkatkan kesejahteraan masyarakat. Namun, keberhasilan implementasinya dipengaruhi oleh beberapa faktor utama seperti kebijakan pemerintah, ketersediaan anggaran, kualitas sumber daya manusia, serta efektivitas sistem distribusi dan pengawasan, sehingga diperlukan sinergi yang kuat antar pemangku kepentingan untuk memastikan keberlanjutan dan optimalisasi program dalam mendukung ketahanan pangan nasional secara berkelanjutan. Kata Kunci: Program MBG, Ketahanan Pangan, Analytic Network Process, Rantai Pasok Pangan, Pemberdayaan UMKM